Aspects on the seasonal dynamics and the vertical distribution of the crustacean zooplankton community and the Dreissena polymorpha larvae in Lake Trichonis - KEHAYIAS, G.; MICHALOUDI, E.; BEXI, A. (Mediterranean Marine Science, 2004)
In Lake Trichonis 9 crustacea species and the molluscan larvae of Dreissena polymorpha were recorded during four seasonal samplings from summer 2002 to spring 2003. Mean integrated values of crustacea abundance ranged from 4.5 to 12.9 ind/L and were mainly dominated by the calanoida Eudiaptomus drieschi. The abundance values recorded, as well as the seasonal dynamics, followed the monoacmic pattern of oligotrophic lakes. However, the presence of Daphnia cucullata, a typical representative of eutrophic lakes, the decrease of the calanoida participation in the crustacea community and the succession in the cladocera community, could probably indicate a tendency towards a change of the trophic condition of Lake Trichonis.Along the vertical axis the maximum abundance of the zooplankton community was recorded in the surface 0-10 m. Mollusca larvae were present in all seasons and their highest abundance was recorded in the surface layer 0-10 m. Temperature, competition and predation seemed to be the main factors regulating vertical distribution.